2007
DOI: 10.1116/1.2748803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bias on surface properties of TiN films fabricated by hollow cathode discharge

Abstract: Titanium nitride ͑TiN͒ films have been deposited on AISI 304 stainless steel substrates using hollow cathode reactive plasma vapor deposition. Titanium is introduced by sputtering the Ti cathode nozzle and TiN is formed in the presence of a nitrogen plasma excited by radio frequency. The substrate bias voltage is varied from 0 to − 300 V to investigate its effect on the mechanical and structural properties of the films. X-ray diffraction results show the formation of TiN ͑111͒ and Ti 2 N ͑220͒ phases in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
2
0
0
Order By: Relevance
“…Regarding orientation relationships at the interfaces of TiN/Al 2 O 3 and TiN/WC, TiN(001)/Al 2 O 3 (0001), TiN(001)/WC(0001), TiN(111)/Al 2 O 3 (0001), and TiN(111)/WC(0001) were selected (Table 1). This is because TiN coatings deposited on various substrate materials including WC were frequently observed to be oriented parallel to (001) and (111) planes of cubic B1 TiN with respect to substrates 13‐18 . Although it has not been reported that TiN coatings deposited on composites containing Al 2 O 3 and WC, the preferred orientations of (001) and (111) planes of TiN on the present Al 2 O 3 –WC composites were confirmed by XRD and EBSD analyses in this study (see Section 3.3).…”
Section: Computational and Experimental Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…Regarding orientation relationships at the interfaces of TiN/Al 2 O 3 and TiN/WC, TiN(001)/Al 2 O 3 (0001), TiN(001)/WC(0001), TiN(111)/Al 2 O 3 (0001), and TiN(111)/WC(0001) were selected (Table 1). This is because TiN coatings deposited on various substrate materials including WC were frequently observed to be oriented parallel to (001) and (111) planes of cubic B1 TiN with respect to substrates 13‐18 . Although it has not been reported that TiN coatings deposited on composites containing Al 2 O 3 and WC, the preferred orientations of (001) and (111) planes of TiN on the present Al 2 O 3 –WC composites were confirmed by XRD and EBSD analyses in this study (see Section 3.3).…”
Section: Computational and Experimental Methodssupporting
confidence: 75%
“…This is because TiN coatings deposited on various substrate materials including WC were frequently observed to be oriented parallel to (001) and (111) planes of cubic B1 TiN with respect to substrates. [13][14][15][16][17][18] Although it has not been reported that TiN coatings deposited on composites containing Al 2 O 3 and WC, the preferred orientations of (001) and (111) planes of TiN on the present Al 2 O 3 -WC composites were confirmed by XRD and EBSD analyses in this study (see Section 3.3). Moreover, (0001) planes of corundum Al 2 O 3 and hexagonal WC crystals are thermodynamically most stable surfaces, 19,20 so that the above interface orientations are most likely involved even in the real Al 2 O 3 -WC composites with TiN coatings.…”
Section: Dft Calculationssupporting
confidence: 66%